Adsorption of Cd(II) from Aqueous Solutions by Cellulose Modified with Maleic Anhydride and Thiourea - Yanmei Zhou; Xiaoyi Hu; Qiang Jin; Xinhai Wang; Tongsen Ma (Adsorption Science & Technology)
In this work, cellulose modified with maleic anhydride and thiourea (CMT) was synthesized as a novel type of adsorbent to remove heavy-metal ion. The synthesized adsorbent was characterized by Fourier transform infrared spectroscopy, elemental analysis, scanning electron microscopy, thermogravimetric analysis and X-ray diffraction. Batch experiments were performed to investigate the influence of different factors on the adsorption of Cd(II) from aqueous solution. Based on the adsorption data, the adsorption isotherm model was confirmed and the maximum adsorption capacity of Cd(II) from the Langmuir model was found to be 94.47 mg g −1 . The adsorption kinetics indicated that the adsorption process followed pseudo-second-order model. Adsorption/desorption experiments for more than six cycles showed the possibility of repeated use of CMT for the adsorption of Cd(II) from aqueous solutions.